Ranging patterns, spatial overlap, and association with dolphin morbillivirus exposure in common bottlenose dolphins (Tursiops truncatus) along the Georgia, USA coast. Issue 24 (26th November 2018) - Balmer, Brian; Zolman, Eric; Rowles, Teri; Smith, Cynthia; Townsend, Forrest; Fauquier, Deborah; George, Clay; Goldstein, Tracey; Hansen, Larry; Quigley, Brian; McFee, Wayne; Morey, Jeanine; et al.
Abstract: During 2013–2015, an outbreak of dolphin morbillivirus (DMV) occurred in the western North Atlantic, which resulted in the stranding of over 1, 600 common bottlenose dolphins (Tursiops truncatus) . There are currently five coastal and 10 bay, sound, and estuary dolphin stocks along the U.S. Atlantic coast, yet there is very limited understanding of which stocks were exposed to DMV during the recent outbreak, or how DMV was transmitted across stocks. In order to address these questions, information is needed on spatial overlap and stock interactions. The goals of this project were to determine ranging patterns, prevalence of DMV, and spatial overlap of the South Carolina‐Georgia (SC‐GA) Coastal Stock, and adjacent Southern Georgia Estuarine System (SGES) Stock. During September 2015, a health assessment and telemetry study was conducted in which 19 dolphins were captured, tested for antibodies to DMV, and satellite tagged. Dolphins were classified into one of three ranging patterns (Coastal, Sound, or Estuary) based upon telemetry data. Coastal dolphins (likely members of the SC‐GA Coastal Stock) had a significantly higher prevalence of positive DMV antibody titers (0.67; N  = 2/3), than Sound and Estuary dolphins (likely members of the SGES Stock) (0.13; N  = 2/16). These results suggest that the SC‐GA Coastal Stock may have experienced greater exposure to DMV as compared to the SGES Stock. However, due to the small size of the SGES Stock and its exposure to high levels of persistent contaminants, this stock may be particularly vulnerable to DMV infection in the future. Abstract : During 2013–2015, an outbreak of dolphin morbillivirus (DMV) occurred in the western North Atlantic in which over 1, 600 common bottlenose dolphins stranded. A health assessment and telemetry study was initiated to assess DMV prevalence and ranging patterns of dolphins along the Georgia coast. The results of this study suggest that spatial overlap between dolphin stocks may play a role in DMV exposure